EVALUATION OF TOTAL ANNUAL COSTS OF HEAT EXCHANGER NETWORKS USING MODIFIED PINCH ANALYSIS (Nigerian Journal of Technology, 2016)
This study presents pinch analysis of some heat exchanger networks (HENs) problems using Hint integration (HINT) software. Three examples reported to have been solved using different approaches by various researchers to obtain the least possible total annual cost (TAC) were solved using the Hint software.  In this work, the use of remaining problem analysis (RPA) contained in the heat integration software was used to carry out matching and the general optimization of the networks for minimum TAC for the three problems solved. The results obtained after solving the first problem using RPA based heat integration gave a minimum total annual cost (TAC) of $237, 510 /yr. which is the fourth when compared with the lowest solution that shows the minimum TAC of $235.400 /yr. in that example. However, the TAC obtained in solving problem  2 and 3 were $562, 333 /yr. and $2.881 M/yr. respectively and they are the least total annual cost obtained when compared with what have been obtained using mathematical programming and non-RPA based Hint software. The overall assessment of the various approaches used to solve these problems when compared with the results obtained in this study shows that HINT software is able to obtain TAC that are within the same range as those obtained using mathematically based technique. http://dx.doi.org/10.4314/njt.v35i3.10